ICAM-1 is a key receptor mediating cytoadherence and pathology in the Plasmodium chabaudi malaria model - Deirdre A. Cunningham; Jing-wen Lin; Thibaut Brugat; William Jarra; Irene Tumwine; Garikai Kushinga; Jai Ramesar; Blandine Franke-Fayard; Jean Langhorne (Malaria Journal, 2017)
Abstract Background Parasite cytoadherence within the microvasculature of tissues and organs of infected individuals is implicated in the pathogenesis of several malaria syndromes. Multiple host receptors may mediate sequestration. The identity of the host receptor(s), or the parasite ligand(s) responsible for sequestration of Plasmodium species other than Plasmodium falciparum is largely unknown. The rodent malaria parasites may be useful to model interactions of parasite species, which lack the var genes with their respective hosts, as other multigene families are shared between the species. The role of the endothelial receptors ICAM-1 and CD36 in cytoadherence and in the development of pathology was investigated in a Plasmodium chabaudi infection in C57BL/6 mice lacking these receptors. The schizont membrane-associated cytoadherence (SMAC) protein of Plasmodium berghei has been shown to exhibit reduced CD36-associated cytoadherence in P. berghei ANKA-infected mice. Methods Parasite tissue sequestration and the development of acute stage pathology in P. chabaudi infections of mice lacking CD36 or ICAM-1, their respective wild type controls, and in infections with mutant P. chabaudi parasites lacking the smac gene were compared. Peripheral blood parasitaemia, red blood cell numbers and weight change were monitored throughout the courses of infection. Imaging of bioluminescent parasites in isolated tissues (spleen, lungs, liver, kidney and gut) was used to measure tissue parasite load. Results This study shows that neither the lack of CD36 nor the deletion of the smac gene from P. chabaudi significantly impacted on acute-stage pathology or parasite sequestration. By contrast, in the absence of ICAM-1, infected animals experience less anaemia and weight loss, reduced parasite accumulation in both spleen and liver and higher peripheral blood parasitaemia during acute stage malaria. The reduction in parasite tissue sequestration in infections of ICAM-1 null mice is maintained after mosquito transmission. Conclusions These results indicate that ICAM-1-mediated cytoadherence is important in the P. chabaudi model of malaria and suggest that for rodent malarias, as for P. falciparum, there may be multiple host and parasite molecules involved in sequestration.